Crosses on the ballot : patterns of British voter alignment since 1885 - Wald, Kenneth D. (Princeton University Press, 1983)
In an exploration of mass voter alignments in Great Britain, Kenneth D. Wald illuminates the electoral consequences of major social divisions and the relationship between social structure and partisanship. He establishes that the transition from religion to social class as the chief influence on British voting occurred after World War I, as most scholars have presumed, rather than before the War, as a number of recent revisionist discussions have claimed. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.